From Bench to Boardroom The R&D Leader's Guide - Spiro, Clifford L.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Copernicus, 2018)
This must-read guide offers a practical and engaging introduction to the ins and outs of R&D leadership. Innovation is a two-trillion-dollar industry, and, on top of the baseline complexity faced by any manager, the R&D or Innovation leader confronts an additional set of challenges. Armed with years of experience in roles ranging from scientist to Vice President of R&D to founder of his own company to innovation career coach, Dr. Clifford L. Spiro shares his insights on a carefully curated selection of topics. This indispensable playbook covers: Building, managing, and motivating a team Setting schedules and goals Assessing and rewarding project success Working with other departments Legal and intellectual property considerations Dr. Spiro's distinctive blend of big-picture strategic thinking and day-to-day, nitty-gritty tips (e.g., Five Great Questions For R&D Managers to Ask Every Time) is essential reading for current and aspiring R&D leaders through seasoned managers as well as anyone at an organization that has an R&D, innovation, or technology transfer component. Providing a prescriptive, in-the-trenches assessment of how to leadinnovation more effectively, this book ably equips the reader to anticipate potential problems and to succeed both within the R&D department and across his or her company.
Foreword -- Glossary.- Dedication.- Preface.- About the Author -- 1 What Do I Mean By "Innovation?" -- 2 Can Anyone, and Should Anyone, Lead Innovation? -- 3 Do You Have What it Takes to Lead Innovation? -- 4 Putting a Good Innovation Team Together -- 5 Getting the Right Portfolio Mix of Projects -- 6 Innovation Project Execution -- 7 Creating a Culture of Creativity -- 8 Creating a Learning Organization -- 9 Human Resource Issues For Innovation Organizations -- 10 Globalization of Innovation and Leading Remote Teams -- 11 Measuring Innovation Effectiveness -- 12 Earning Followership -- 13 Patents and Intellectual Property -- 14 Acquiring and Integrating Technology -- 15 The C-Suite, the Boardroom, and Beyond -- 16 Closing Thoughts.
Keywords: Technology -- Sociological aspects; Economic development; Strategic planning; Leadership; Business; Management science; Operations research; Science, Technology and Society; Economic Development, Innovation and Growth; Business Strategy and Leadership; Business and Management; Operations Research, Management Science